H-Type Hypertension Is a Risk Factor for Cerebral Small-Vessel Disease. (7th February 2020) - Li, Tan; Liu, Xueyun; Diao, Shanshan; Kong, Yan; Duan, Xiaoyu; Yang, Si; Liu, Sanjiao; Fang, Qi; Cai, Xiuying
Abstract : Background . The correlation between H-type hypertension and cerebral small-vessel diseases (CSVD) remains uncertain. Objective . The present study was designed to explore the possible relationship between H-type hypertension and CSVD spectrum and total burden. Method . We included 329 patients in the present study and divided them into four groups: the H-type hypertension group, isolated hypertension group, isolated hyperhomocysteinemia (HHcy) group, and control group. Clinical variables of interest and the MR examination sequences were obtained. We counted the presence of each CSVD feature and rated the total burden of CSVD on an ordinal scale from 0 to 4 according to a recent described score rule. Result . The results showed that H-type hypertension was associated with the presence of cerebral microbleeds (CMBs), and the severity of white-matter hyperintensities (WMHs) and peripheral vascular space (PVS). CSVD total burden was significantly related to age (OR: 1.059, 95% CI: 1.037–1.082), systolic pressure (OR: 1.122, 95% CI: 1.007–1.136), triglycerides (OR: 1.386, 95% CI: 1.037–1.854), isolated HHcy (OR: 4.154, 95% CI 1.836–9.401), and H-type hypertension (OR: 5.028, 95% CI: 2.323–10.883). Also, we further observed hypertension and HHcy had a synergistic effect on CSVD total burden (OR: 2.776, 95% CI: 1.564–4.927). Conclusion . H-type hypertension was associated with CSVD total burden and CSVD spectrum, which deserves further prevention measures. Furthermore, hypertension and HHcy had a synergistic effect on CSVD total burden.